AN OPTICAL COHERENCE TOMOGRAPHY EVALUATION OF TWO SYNTHETIC BONE AUGMENTATION MATERIALS IN CALVARIA AND MANDIBULAR LAB RATS CAVITIES - Ruxandra Elena Caracaș; Eugen Osiac; Lucian Toma Ciocan; Dan Eduard Mihăiescu; Sandra Alice Buteică; Ioana Mitruț; Andrei Mihai Caracaș; Alex Ioan Sălan; Maria Alexandra Drăghici; Horia Octavian Manolea (Romanian Society of Oral Rehabilitation, 2021)
The aim of this study was the evaluation of the osseointegration degree of two synthetic bone augmentation materials, a commercial product and an experimental one, using the optical coherence tomography. We made two study groups composed of 8 laboratory Whistar rats on which we created experimental cavities with a diameter of 3 mm at the level of the parietal bone and mandible. Samples were obtained from both calvaria and the mandible of the animals after two months for first study group and after four months for the other. Optical coherence tomography (OCT) was used for a non-destructive evaluation of the surface and subsurface of bone tissue. The results of our study showed in general a good integration of the inserted materials; in some cases the healing of the augmented cavities with the experimental material was faster, while the commercial material offered a more reproducible healing pattern.